Pandemic Rumination and Resilience on Frontline Health Care Professionals in India: A Cross-Sectional Survey - Vadi, Sonali; Rungta, Neha; Shah, Sagar; Pednekar, Ashwini (Archives of Clinical and Biomedical Research, 2022)
Background High workload during pandemic has caused psychological stress in Healthcare Professionals (HCPs). It is necessary to identify factors that lead to negative mental health effects, and those that create resilience to withstand stress. Aim: We examined relationship between stress & perseverative thinking, and social networking & resilience in HCPs working in Emergency Room (ER) and intensive care unit (ICU). Methods Cross-sectional survey conducted from 15th April-15th May, 2021 using questionnaire with clinically-validated scales: WHO 5 Well-being Index, Brief Resilience Scale (BRS), UCLA Loneliness Scale, Perseverative Thinking Questionnaire (PTQ), Impact of Event Scale – 6 (IES 6), and Berkman-Syme Social Networking Index (SNI). We analysed effect of age, location of work, marital status, and participation in community activity on these indices. Results 39.6% had low resilience, 34.8% had high impact of pandemic. BRS and IES 6 score varied significantly when classified according to age and marital status (p<0.05). WHO-5 Wellbeing Index was negatively correlated with UCLA Loneliness Scale, PTQ and IES 6 (p<0.05). SNI and BRS was negatively correlated with UCLA loneliness scale (p<0.05). Conclusions Perseverative thinking exacerbates burden of ongoing stressors counteractive to psychological well-being. Modifiable factor, our findings underscore value of helping frontline HCPs manage these circumstances.